المصادر اللغوية في تخمين معاني المفردات: دراسة في قراءة النصوص العربية = Linguistic sources in guessing word meaning: a study in reading arabic texts - Zulkifli, Hidayatul Hasanah; Mustapha, Nik Hanan (2012)
Guessing word meaning from context plays an important role in increasing the level of reading comprehension of second or foreign language learners. Despite various taxonomies for guessing word meanings, most of them generally fall into two categories: linguistic sources, and non-linguistic sources. Considering the importance of such a study in Arabic language, this study investigates the use of second language sources within the linguistic category in guessing the meaning of words. Ten university students participated in this introspective study by performing reading tasks on selected Arabic texts. A set of data was gathered through a think aloud process and interviews, which was later analyzed based on Bengeleil and Paribakht’s taxanomy (2004). The study concludes with some findings that explain how students utilize linguistic sources when guessing the meanings of word while performing reading tasks.